Prototype Design of E-BMX 2000 Watt Electric Motorcycle - Utsman Syah Amrullah; Rilis Eka Perkasa; Muhammad Fakhruddin (Logic : Jurnal Rancang Bangun dan Teknologi, 2023)
Limited supplies of fossil fuels such as gasoline, diesel and LPG resulting in vehicles that use internal combustion would be abandoned and replaced by electric vehicles. There have been many coverages that have reviewed the advantages of electric vehicles, where the advantages of electric vehicles include simple mechanical components, relatively low pollution, low noise levels, and could become a solution for future vehicles for an environmentally friendly life. This study aims to design and build a motorcycle prototype, a work which includes the design and manufacture of a BMX type motorcycle frame powered by a 2000 watt BLDC motor power, and testing the performance of the prototype using dynotest and compared to conventional motorcycles to compare the performance characteristics of both motorcycle. The frame is designed using Solidworks, then manufactured by cutting, bending, drilling, welding, and painting process. Mechanical components include frames that use mild steel pipes with diameter of 1.5 inches and thickness of 1.2 mm. Other mechanical components use components available on the market, such as headsets, front forks, disc brakes, hydraulic caliper brakes, and wheel assemblies. The electrical components used are 48V 2000-watt QS Motor, 60V 15 Ah Lithium battery, Yuyangking 80A controller and electric gas throttle with voltage indicator. The results of the dynotest show that the maximum torque reaches 204 NM (roller) which is achieved at 976 rpm. The maximum speed reaches 69.7 Km/hour. The range of the single-charged battery could cover a distance of 30 km. The characteristic of 2000 Watt E-BMX is very powerful at low revs and stable at high revs, shown by achieving maximum torque at low RPM. To save battery life, it is necessary to limit the remaining voltage, which is done at 55 Volts, so that the battery do not completely run out. It could be concluded that electric motorcycle developed in this study is suitable for use in urban areas (paved tracks or light off-road) with determined mileage and the path travelled, and battery management is needed so the battery does not run out in the middle of a trip.